2016
DOI: 10.1007/s10620-016-4414-9
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Healthcare Utilization Among Veterans with Inflammatory Bowel Disease

Abstract: We found that current tobacco use, age <40 at first IBD visit, UC pancolitis, and CD fistuilizing phenotype in addition to Caucasian and African-American race were independent predictors of increased healthcare utilization. Interventions should be targeted at these groups to decrease healthcare utilization and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
8
1
Order By: Relevance
“…2 The total annual financial burden of IBD on the healthcare system has been estimated as anywhere from $6 billion to over $30 billion, with slightly more than half attributed to CD, 4,5 a cost that has rapidly increased over the past 2 decades. 2,6,7 There is growing appreciation that a small subgroup of IBD patients contributes disproportionately to the overall economic burden of IBD on the healthcare systems. 4,[8][9][10][11] These refractory, high-utilizing IBD patients are generally resistant/intolerant to medical therapy and, as a result of failing to achieve and maintain a medically induced remission, require extensive and repeated operations to address complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The total annual financial burden of IBD on the healthcare system has been estimated as anywhere from $6 billion to over $30 billion, with slightly more than half attributed to CD, 4,5 a cost that has rapidly increased over the past 2 decades. 2,6,7 There is growing appreciation that a small subgroup of IBD patients contributes disproportionately to the overall economic burden of IBD on the healthcare systems. 4,[8][9][10][11] These refractory, high-utilizing IBD patients are generally resistant/intolerant to medical therapy and, as a result of failing to achieve and maintain a medically induced remission, require extensive and repeated operations to address complications.…”
Section: Introductionmentioning
confidence: 99%
“…In the US alone, it is estimated that there are 1.8 million annual IBD‐related outpatient encounters and 75,000 emergency room visits, numbers that have been steadily increasing 2 . The total annual financial burden of IBD on the healthcare system has been estimated as anywhere from $6 billion to over $30 billion, with slightly more than half attributed to CD, 4,5 a cost that has rapidly increased over the past 2 decades 2,6,7 …”
Section: Introductionmentioning
confidence: 99%
“…UC occurs more frequently than Crohn’s disease [ 11 ] and damage to the mucosal layer is thought to be the main cause [ 12 , 13 ]. The healthcare cost associated with management is considerable, especially in the USA, Europe and Asian countries [ 14 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both Black and Hispanic inflammatory bowel disease (IBD) patients were less likely to be referred for specialist visits compared to white patients. 5 Outside of GI, a 2017 study of neurology care found that Black and Hispanic patients were 30% and 40% less likely, respectively, to see an outpatient neurologist relative to white controls, even after adjustment for socioeconomic status. 6 Another study examining post-discharge healthcare utilization after trauma found that African American patients was significantly less likely to use post-discharge healthcare services than white patients.…”
Section: Discussionmentioning
confidence: 99%